Current biochemical treatments of mitochondrial respiratory chain disorders. (3rd June 2019) - Heaton, Robert; Millichap, Lauren; Saleem, Fatima; Gannon, Jennifer; Begum, Gemma; Hargreaves, Iain P.
ABSTRACT: Introduction : The clinical heterogeneity and unpredictable clinical course of mitochondrial respiratory chain (MRC) disorders have hindered the development of effective therapeutic strategies for the treatment of these diseases. Treatment generally involves supportive therapy aimed at enhancing mitochondrial function as well as ameliorating increased reactive oxygen species (ROS) generation which is associated with MRC dysfunction. The purpose of this review is to focus on current biochemical strategies together with those that are being developed to the treatment of MRC disorders. Areas covered : This review focusses on the biochemical strategies that have been developed to augment MRC function (increase electron transport and substrate availability in the MRC), scavenge ROS (antioxidant therapies) and modify mitochondrial biogenesis will be covered. The authors have comprehensively reviewed the literature to provide up to date information on these subjects. Expert opinion : A consensus needs to be reached on the treatment of MRC disorders, and rather than the use of generic 'antioxidant cocktails' case-specific therapeutic strategies should be considered for the treatment patients. The inclusion of pharmacotherapies that target MRC function, cellular antioxidant status and mitochondrial biogenesis in the treatment regime of patients may be appropriate to ameliorate the defects in these parameters that contribute to disease pathophysiology.